Nipah Virus – Thread to Pregnancy - Kumar, Sujeet; BHATIA, Shubham; Sharma, Amit; painuly, Neelam (Asian Journal of Pharmaceutical Research and Development, 2018)
Nipah virus is a type of zoonotic virus. Which cause serious respiratory nervous problems along with serious fever it get easily transmitted to one infected person to another person. Nipah virus is a great thread to mankind. Nipah virus belong to the family of Paramyxoviridae. Nipah virus positive person is called as NiV positive pigs various birds are also effected by the virus badly. So the study and proper knowledge about Nipah virus should be their.